Neurobiologically based interventions for autism spectrum disorders-rationale and new directions - Poustka, L.; Brandeis, D.; Hohmann, S.; Holtmann, M.; Bolte, Sven; Banaschewski, T. (I O S Press, 2014)
Autism spectrum disorders (ASD) are heterogeneous, neurodevelopmental disorders with early onset, characterized by a triad of impairments in reciprocal interaction and communication as well as repetitive and restricted interests and activities. Though underlying causes still remain largely unknown, there is now evidence for abnormal growth trajectories in the early brain development in ASD during vulnerable periods and subsequent impairment of neuronal organization and differentiation of neuronal networks. A growing number of studies over the last 10 years support the efficacy of behaviorally based interventions in ASD for the improvement of social communication and behavioral functioning. In contrast, research on neurobiologically based therapies for ASD is still at its beginnings. In this article, we will provide a selective overview of novel interventions and trainings based on neurobiological principles. Directions and options for future research on treatment aiming at restoration of normal plasticity in disrupted brain circuits in ASD are discussed. © 2014 - IOS Press and the authors. All rights reserved.